The Benefits Of Water In The Quran - Rahmahyani; Siti Ramadhani; Ali Akbar (Jurnal Riset Multidisiplin Edukasi, 2025)
Water is a form of gift from God for creatures on this earth and as the source of this life. This paper aims to explore the concept of water in the perspective of the Qur'an, science and medicine. This research is a qualitative research using content analysis method. The data sources for this research are the Qur'an and literature books related to the nature of water according to science and medicine. The collected literature studies will be categorized, reduced, compared, verified and finally concluded. The results of this study confirm that; First; The Qur'an provides instructions for humans to think, reflect, live, and see everything that Allah has created for humans and that Allah made all living things from water. Second; There is a relationship between the Qur'an and medical science about water and the benefits of water for health. Third; Water has behavior like living things, this can be seen from the research conducted by Dr. Masaru Emoto from Yokohama University, who researched the shape of the water molecule and found that the shape of the water molecule that is recited by prayer will be beautiful.